Effects of mobile phone radiation (900 MHz radiofrequency) on structure and functions of rat brain. (December 2014) - Saikhedkar, Nidhi; Bhatnagar, Maheep; Jain, Ayushi; Sukhwal, Pooja; Sharma, Chhavi; Jaiswal, Neha
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The goals of this study were: (1) to obtain basic information about the effects of long-term use of mobile phones on cytological makeup of the hippocampus in rat brains (2) to evaluate the effects on antioxidant status, and (3) to evaluate the effects on cognitive behavior particularly on learning and memory. Methods: Rats (age 30 days, 120 ± 5 g) were exposed to 900 MHz radio waves by means of a mobile hand set for 4 hours per day for 15 days. Effects on anxiety, spatial learning, and memory were studied using the open field test, the elevated plus maze, the Morris water maze (MWM), and the classic maze test. Effects on brain antioxidant status were also studied. Cresyl violet staining was done to assess the neuronal damage. Result: A significant change in behavior, i.e., more anxiety and poor learning was shown by test animals as compared to controls and sham group. A significant change in the level of antioxidant enzymes and non-enzymatic antioxidants, and an increase in lipid peroxidation were observed in the test rats. Histological examination showed neurodegenerative cells in hippocampal sub regions and the cerebral cortex. Discussion: Thus our findings indicate extensive neurodegeneration on exposure to radio waves. Increased production of reactive oxygen species due to exhaustion of enzymatic and non-enzymatic antioxidants and increased lipid peroxidation indicate extensive neurodegeneration in selective areas of CA1, CA3, DG, and the cerebral cortex. This extensive neuronal damage results in alterations in behavior related to memory and learning.